Brace treatment for scoliosis secondary to chiari malformation type 1 or syringomyelia without neurosurgical intervention: A matched comparison with idiopathic scoliosis - Zhang, Tianyuan; Bao, Hongda; Zhang, Xin; Shu, Shibin; Liu, Zhen; Sun, Xu; Qiu, Yong; Zhu, Zezhang (European spine journal, 2021)
Purpose To evaluate the effectiveness of brace treatment in patients with Chiari malformation type 1 (CM-1) or syringomyelia associated scoliosis without neurosurgical intervention. Methods This was a retrospective case–control study. 34 CM-1 or syringomyelia (CMS) patients who received brace treatment without neurosurgical intervention were recruited. Another 68 matched patients with idiopathic scoliosis who received bracing served as the control group. The matching criteria included gender, age (± 1 years), Risser sign (± 1 grade), initial curve magnitude (± 5°), curve patterns and follow-up time (± 6 months). Patients who encountered curve progression and scoliosis surgery were compared between different groups. Results Until the last visit, 16 (47%) patients in CMS group and 18 (26%) patients in IS group occurred curve progression; 9 (26%) patients and 15 (22%) patients underwent scoliosis surgery, respectively. Compared to idiopathic scoliosis, patients with CMS-associated scoliosis had a significantly higher rate of curve progression ( P = 0.038). However, no significant difference was observed between two groups regarding to the rate of surgery ( P = 0.867). Patients with combined CM-1 and syringomyelia had a higher rate of surgery than patients with isolated CM-1 or syringomyelia ( P = 0.049). The double major curve pattern was identified as the risk factor for curve progression. Conclusion Brace treatment is effective for CMS-associated scoliosis without neurosurgical intervention. Compared to idiopathic scoliosis, brace can provide similar prevention for scoliosis surgery in CMS patients, but slight or moderate curve progression may occur. Specifically, patients with combined CM-1 and syringomyelia should be followed closely with a higher expectation of curve progression.